Improvement of SLA Parameters in Virtual Machine Migration by using Genetic Algorithm - Thind, Anu; Devgan, Mandeep (International Journal of Computer Sciences and Engineering, 2025)
Virtualization plays a main role in the cloud computing technology, usually in the cloud computing, users share the data there in the clouds like application etc., but with virtualization users shares the communications. A general technique to enhance the energy proficiency of a datacentre is VM placement by coordinating the quantity of dynamic servers to the present needs of the VMs and setting the remaining servers in low-control standby modes using SLA violations .In cloud computing environments, cloud service users consume cloud resources as a service and pay for service use. Before a cloud provider provisions a service to a consumer, the cloud provider and consumer (or broker) need to establish a service level agreement. So this work explored the utilization of VM migration with GA algorithm in MATLAB environment. We found the performance parameters like Number of VMs, Response time, Throughput and Execution Time.